Supply Chain Integration, Accounting Information System Quality, and MSME Operational Performance: A Supply Chain Risk Mediation Approach - Handriyani Dwilita; Iskandar Muda (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the effect of Supply Chain Integration and the Quality of Accounting Information Systems on Operational Performance with Supply Chain Risk as a mediating variable. The study uses a quantitative approach with an explanatory design. The study population is MSMEs in the food & beverage sector in one of the districts in Medan City. Sampling using purposive sampling technique and obtained 42 respondents with questionnaires eligible to be tested. The research data is primary data collected through questionnaire distribution and analyzed using multiple linear regression techniques based on a mediation model or MRA, with direct and indirect effects testing using the Sobel test. The results revealed that simultaneously the variables Supply Chain Integration and the Quality of Accounting Information Systems affect Operational Performance, but partially only the Supply Chain Integration variable affects Operational Performance. The mediation test showed that Supply Chain Integration and the Quality of Accounting Information Systems have a negative effect on Supply Chain Risk. This indicates that increasing Supply Chain Integration and the Quality of Accounting Information Systems can reduce exposure to Supply Chain Risk. However, Supply Chain Risk cannot mediate the relationship between Supply Chain Integration and the Quality of Accounting Information Systems on Operational Performance. These findings demonstrate that operational performance in MSMEs is improved more through the influence of supply chain integration and the quality of accounting information systems than through supply chain risk mitigation mechanisms.